Efficacy of early enteral feeding with supplemented mother’s milk on postoperative outcomes of cardiac surgical infants: A randomized controlled trial - Anuradha Singal; Manoj Kumar Sahu; Geeta Trilok Kumar; Bani Tamber Aeri; Mala Manral; Anuja Agarwala; Shivam Pandey (Annals of Pediatric Cardiology)
Introduction: Congenital heart disease (CHD)-associated malnutrition is a systemic consequence of CHD. Dietary recommendations to fulfill nutritional requirements are lacking. This randomized controlled trial (RCT) was conducted to determine the efficacy of early enteral feeding with supplemented expressed breast milk (suppl-EBM) versus expressed breast milk (EBM) in improving the weight of postoperative cardiac surgical infants. Objective: The primary objective was the weight change between the EBM group and the suppl-EBM group at the 15th postoperative day (POD) or intensive care unit (ICU) discharge. The secondary objectives were to compare the ventilation duration (VD), length of ICU stay (LOICUS), length of hospital stay (LOHS), macronutrient consumption, adverse events, sepsis, and mortality between the two groups. Materials and Methods: This study was a parallel-group, open-labeled, single-blinded, variable block size RCT conducted at a tertiary care teaching hospital in northern India. Full-term breastfed infants ≤6 months, weighing ≥2.5 kg at birth, and undergoing congenital cardiac repair were enrolled in this study. The infants were fed either EBM or supplemented EBM in control and intervention groups, respectively. Weight and length were measured at baseline and 15th POD or at ICU discharge. Biochemical parameters at baseline and every alternate day, sepsis parameters every third POD and VD, LOICUS, LOHS, macronutrient consumption, and adverse events were assessed daily. Results: The mean weight, weight change percentage, and weight for age z score were significantly higher in the supplemented EBM group (P < 0.05). The macronutrient consumption was significantly higher in the intervention group (P < 0.05). No significant difference was found between the two groups for VD, LOICUS, and LOHS (P > 0.05). The sepsis was higher in the EBM group. However, the mortality rate did not differ between the two groups (P > 0.05). Conclusion: Supplemented feeding may improve the weight of postoperative cardiac infants with no serious adverse events.